1979
DOI: 10.1126/science.205.4408.806
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Level Lowering During the Illinoian Glaciation: Evidence from a Bahama "Blue Hole"

Abstract: Stalagmites have been recovered from 45 meters below sea level in an underwater karstic cave ("blue hole") near Andros Island in the Bahamas. Uranium series ages, corrected for contamination of the sample by young marine carbonate replacements, show that the speleothem was deposited between 160,000 and 139,000 years before the present. This period corresponds to the Illinoian glacial event and demonstrates that sea level must have been lowered by at least 42 meters (allowing for subsidence) from its present po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 12 publications
1
65
0
1
Order By: Relevance
“…At Moomomi, the sand itself, whether consolidated or not, is thought to have been "derived from the former marginal sea floor when it was bared during the Waipio low stand of the sea" (Stearns and Macdonald, 1947), which according to Stearns (1978) is of Illinoian age. At this time, sea level was evidently about 107 m (350 feet) lower than at present (Gascoyne et al, 1979). Most of the fossil sites at Moomomi are at elevations higher than Site I.…”
Section: Molokaimentioning
confidence: 61%
See 1 more Smart Citation
“…At Moomomi, the sand itself, whether consolidated or not, is thought to have been "derived from the former marginal sea floor when it was bared during the Waipio low stand of the sea" (Stearns and Macdonald, 1947), which according to Stearns (1978) is of Illinoian age. At this time, sea level was evidently about 107 m (350 feet) lower than at present (Gascoyne et al, 1979). Most of the fossil sites at Moomomi are at elevations higher than Site I.…”
Section: Molokaimentioning
confidence: 61%
“…During the Wisconsinan glacial period, a maximum glacioeustatic lowering of sea level of approximately 120 m (394 feet) was reached approximately 17,000 years ago (Gascoyne et al, 1979). The shallow channels that now separate Molokai, Maui, and Lanai were then dry land, joining what are presently three islands into a single large island, "Maui Nui" (Big Maui).…”
Section: Geology and Physiographymentioning
confidence: 99%
“…The growth of continental glaciers during the Pleistocene decreased ocean volume, causing a reduction in sea level of about 160 m during the middle Pleistocene (Gascoyne et al, 1979) and 120 m during the last glacial maximum (Hopkins, 1982;Yang and Xie, 1984). In the absence of tectonic activity, land area during the last glacial maximum can be estimated simply by tracing the 120 m bathymetric line; all areas above that level were dry land about 18 000 years ago.…”
Section: Sea Level and Land Areamentioning
confidence: 99%
“…Much of the speleothem evidence used to constrain the height and timing of Quaternary sea level-changes is based on two types of material: 'drowned' stalactites, stalagmites and fl owstones formed in previously air-fi lled passages and now below sea level (Gascoyne et al, 1979;Li et al, 1989;Richards et al, 1992;Richards et al, 1994), and biogenic marine overgrowths on speleothems (MOS), frequently found in many coastal caves (Harmon et al, 1978;Bard et al, 2002;Antonioli et al, 2004;Suric et al, 2007).…”
Section: Introductionmentioning
confidence: 99%